Introducing Tuak, the Traditional Alcoholic Beverage of the Dayak Muara Tribe in Kalimantan, Indonesia: Gastronomy Identity Unveiled - Sari, Wiwik Nirmala; Elsty, Kezia (Al Makki Publisher, 2024)
This research explores the potential of the traditional alcoholic beverage